Chart for visual acuity screening. Issue 6 (June 1989) - Wong, D.; Kaye, S. B.
Abstract : The statistical basis underlying the use of several visual acuity charts is examined. A new chart which offers theoretical and practical advantages for visual acuity screening is described.